Determination of Fructan (Inulin, FOS, Levan, and Branched Fructan) in Animal Food (Animal Feed, Pet Food, and Ingredients): Single-Laboratory Validation, First Action 2018.07. (23rd November 2019) - McCleary, Barry V; Charmier, Lucie M J; McKie, Vincent A; McLoughlin, Ciara; Rogowski, Artur
Abstract: Traditional enzyme-based methods for measurement of fructan were designed to measure just inulin and branched-type (agave) fructans. The enzymes employed, namely exo-inulinase and endo-inulinase, give incompletely hydrolysis of levan. Levan hydrolysis requires a third enzyme, endo-levanase. This paper describes a method and commercial test kit (Megazyme Fructan Assay Kit) for the determination of all types of fructan (inulin, levan, and branched) in a variety of animal feeds and pet foods. The method has been validated in a single laboratory for analysis of pure inulin, agave fructan, levan, and a range of fructan containing samples. Quantification is based on complete hydrolysis of fructan to fructose and glucose by a mixture of exo-inulinase, endo-inulinase, and endo-levanase, followed by measurement of these sugars using the PAHBAH reducing sugar method which gives the same color response with fructose and glucose. Before hydrolysis of fructan, interfering sucrose and starch in the sample are specifically hydrolyzed and removed by borohydride reduction. The single-laboratory validation (SLV) outlined in this document was performed on commercially available inulin (Raftiline) and agave fructan (Frutafit®), levan purified from Timothy grass, two grass samples, a sample of legume hay, two animal feeds and two barley flours, one of which (Barley MAX®) was genetically enriched in fructan through plant breeding. Parameters examined during the validation included working range, target selectivity, recovery, LOD, LOQ, trueness (bias), precision (repeatability and intermediate precision), robustness, and stability. The method is robust, quick, and simple.